2009
DOI: 10.1161/circulationaha.108.826230
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Identifies Extensive Downregulation of Noncollagen Extracellular Matrix and Profibrotic Growth Factor Genes in Chronic Isolated Mitral Regurgitation in the Dog

Abstract: Background The volume overload of isolated mitral regurgitation (MR) in the dog results in left ventricular (LV) dilatation and interstitial collagen loss. To better understand the mechanism of collagen loss we performed a gene array and overlaid regulated genes into Ingenuity Pathway Analysis (IPA). Methods and Results Gene arrays from LV tissue were compared in 4 dogs prior to and 4 months after MR. Cine-magnetic resonance-derived LV end-diastolic volume increased 2-fold (p=0.005) and LV ejection fraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
105
2
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(110 citation statements)
references
References 45 publications
1
105
2
2
Order By: Relevance
“…30 There is also downregulation of elastin proteins, fibrillin-1 and fibulin-1, as well as decorin, which regulates collagen fiber assembly. 31 Both tenascin-C and periostin levels are also increased, facilitating slippage between the cardiomyocytes and ECM. This is accompanied by the upregulation of inflammatory signals and downregulation of profibrotic cytokines such as TGF-β and CTGF.…”
Section: Volume Overloadmentioning
confidence: 99%
See 1 more Smart Citation
“…30 There is also downregulation of elastin proteins, fibrillin-1 and fibulin-1, as well as decorin, which regulates collagen fiber assembly. 31 Both tenascin-C and periostin levels are also increased, facilitating slippage between the cardiomyocytes and ECM. This is accompanied by the upregulation of inflammatory signals and downregulation of profibrotic cytokines such as TGF-β and CTGF.…”
Section: Volume Overloadmentioning
confidence: 99%
“…This is accompanied by the upregulation of inflammatory signals and downregulation of profibrotic cytokines such as TGF-β and CTGF. 31 …”
Section: Volume Overloadmentioning
confidence: 99%
“…Increased matrix metalloproteinase activity is associated with progressive LV dilatation and extracellular matrix degradation, contractile dysfunction, and neurohormonal activation in volume overload animal models. Zheng et al, 32 using a gene array analysis, reported recently that eccentric LV remodeling in isolated MR was associated with increased matrix metalloproteinase activity. However, we could not find a significant difference in matrix metalloproteinase families among the groups.…”
Section: Mechanism For LV Remodeling In Mrmentioning
confidence: 99%
“…Most of these studies have been performed on tissue samples taken from the diseased hearts (Oyama et al 2005, Disatian et al 2008, Zheng et al 2009, Aupperle et al 2010, Obayashi et al 2011. The major drawback of these studies is the difficult in vivo acquisition of diagnostic material via i.e.…”
Section: Introductionmentioning
confidence: 99%